A revaluation of the seismicity in the Antarctic - Kaminuma, Katsutada (National Institute of Polar Research, 2000)
P(論文) The Antarctic Peninsula region and some volcanic regions in the Antarctic plate are regions of which the tectonic evolution has been well studied Occurences of tectonic and volcanic earthquakes in the region have been discussed from the point of view of seismotectonics As the number of seismic stations in the world has increased, so has the number of tectonic earthquakes detected in the Antarctic The seismic activity in the following three regions can be discussed from the point of view of seismotectonics or neotectomcs 1) the great earthquakes in the intraplate low seismic region, 2) microseismic activity at the edge of the continent and 3) seismic activity in Wilkes Land Some tectonic earthquakes in these regions are caused by tectonic stress accumulated by crustal deformation after deglaciation The effect of ice sheet change in Antarctica has caused such phenomena as crustal deformation, earthquake occurrence etc in the crust and upper mantle departmental bulletin paper